2014
DOI: 10.1159/000363190
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Human Papilloma Virus-Related Head and Neck Squamous Cell Carcinoma of an Unknown Primary Site

Abstract: Purpose: Head and neck squamous cell carcinoma of an unknown primary site (HNSCCUP) is a heterogeneous group of tumors that includes the human papillomavirus (HPV)-associated oropharyngeal squamous cell carcinoma. To investigate the relationship between HNSCCUP and HPV, we reviewed p16 overexpression and HPV DNA in lymph node metastases and examined their correlation with the primary site and clinical features. Materials and Methods: Thirty-three patients with HNSCCUP were retrospectively studied. Dissected ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…One can even suggest that HNCUP could be considered a subtype of these cancers, since they are the most common occult primary, having cystic metastasis in the same area of the neck with similar age and prognostic panorama. The reported HPV prevalence for HNCUP differs widely in previous studies, between 22 and 91% [11, 12, 23, 24]. Larger studies are needed to better define the HPV prevalence and, it probably varies in different parts of the world and over time.…”
Section: Discussionmentioning
confidence: 93%
“…One can even suggest that HNCUP could be considered a subtype of these cancers, since they are the most common occult primary, having cystic metastasis in the same area of the neck with similar age and prognostic panorama. The reported HPV prevalence for HNCUP differs widely in previous studies, between 22 and 91% [11, 12, 23, 24]. Larger studies are needed to better define the HPV prevalence and, it probably varies in different parts of the world and over time.…”
Section: Discussionmentioning
confidence: 93%
“…The traditional profile of a patient with SCCUP was that of a middle-aged (50-65 years) white men, with heavy smoking and alcohol abuse history. 6,16,17,20 The male predominance correlates with the ease of female-to-male HPV transmission which is precipitated by the high number of sexual partners and oral sex encounters. 6,16,17,20 The male predominance correlates with the ease of female-to-male HPV transmission which is precipitated by the high number of sexual partners and oral sex encounters.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…6,16,17,20 The male predominance correlates with the ease of female-to-male HPV transmission which is precipitated by the high number of sexual partners and oral sex encounters. 16,17,19,20,[22][23][24] However, one retrospective analysis of a small series of patients showed that the HPV status does not correlate with neck stage at presentation. The clinical N classification at diagnosis is usually N2/N3 (11%-95%).…”
Section: Clinical Presentationmentioning
confidence: 99%
“…The diagnostic potential and prognostic role of imaging biomarkers for HPV status in OPC remains unclear. Several previous studies have demonstrated differences between HPV+ and HPV- OPC using anatomic imaging techniques, including CT and MRI [10,11,12,13]. These distinguishing imaging features include a tendency for HPV+ OPC to present with smaller, well-defined primary tumors and cystic nodal metastases.…”
Section: Introductionmentioning
confidence: 99%